Pedestrian circulations: urban ethnography, the mobilities paradigm and outreach work. (7th August 2016) - Smith, Robin James; Hall, Tom
Abstract: This article considers the intersection of urban ethnography, Interactionism and the mobilities paradigm. In its course, we develop a discussion of mobilities as a social order, replete with constraints, conditions and contradictions, in dialogue with Goffman's understanding of interaction order and, more specifically, his remarks on territories and social relations. We draw on ethnographic work undertaken with a team of 'outreach' professionals tasked to care for the street homeless in the UK city of Cardiff. The team enact their duty of care through a repeated patrolling of the city centre, in the course of which they aim to encounter clients and engage them in the provision of immediate services and in planning for support that might meet their needs in the longer term. Outreach workers are street-level bureaucrats then, in a literal sense; they work out of doors and on the move, and lack the sureties of office space – their clients, for their part, lack the sureties of fixed abode. In this context, outreach workers must move through and make use of everyday city space, as they find it; they must also find their clients – searching them out repeatedly, wherever they might turn out to be. The article describes searching and patrol as distinctive mobility practices, and combines this description with reflections on ways to move beyond the sedentary tendency in Goffman's (and others') work. We close by recommending the everyday as locus of inquiry for considerations of the future city and, indeed, for directions of future travel for a mobilities-oriented street-level ethnographic inquiry.